2020
DOI: 10.1016/j.jinf.2020.03.062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corticosteroid treatment on patients with coronavirus infection: a systematic review and meta-analysis

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
328
3
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(359 citation statements)
references
References 25 publications
5
328
3
23
Order By: Relevance
“…We compared our review with another published systematic review addressing corticosteroid therapy in COVID-19. 85 Apart from COVID-19, SARS and MERS, our review included 3 additional populations: ARDS, CAP and influenza. We updated our search until Apr.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our review with another published systematic review addressing corticosteroid therapy in COVID-19. 85 Apart from COVID-19, SARS and MERS, our review included 3 additional populations: ARDS, CAP and influenza. We updated our search until Apr.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al, conducted a systematic review and meta-analysis concluding that CS use is associated with increased lung injury or shock and mortality in patients with CoV-pneumonia [72]. Although intranasal CSs are not recommended for sudden and severe smell loss in COVID-19 patients, when they are receiving them for the treatment of sinonasal diseases, such as rhinitis or chronic rhinosinusitis, drug discontinuation is not recommended [73].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The study found no statistically signi cant association between treatment with corticosteroids and virus clearance time (Hazards ratio (HR), 1.26; 95% CI, 0.58 to 2.74), hospital length of stay (HR, 0.77; 95% CI, 0.33 to 1.78), or duration of symptoms (HR, 0.86; 95% CI, 0.40 to 1.83) [34]. A recent meta-analysis also suggested a higher relative risk for mortality and longer length of stay in patients with SARS-CoV and MERS-CoV treated with corticosteroids [35].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The study concluded the superior effect of arbidol over lopinavir/ritonavir in the treatment of cases with mild to moderate SARS-CoV infection [44]. In another RCT, 86 patients with mild to moderate SARS-CoV-2 infection were randomly assigned to the lopinavir/ritonavir group (34) or the arbidol group (35) or the no antiviral drug group (17). The primary end point was virological cure.…”
Section: Other Antiviral Drugsmentioning
confidence: 99%